2013
DOI: 10.1158/1535-7163.mct-12-1125
|View full text |Cite
|
Sign up to set email alerts
|

Y-box Binding Protein-1 Contributes to Both HER2/ErbB2 Expression and Lapatinib Sensitivity in Human Gastric Cancer Cells

Abstract: Gene amplification of HER2/ErbB2 occurs in gastric cancer and the therapeutic efficacy of the HER2-targeted antibody, trastuzumab, has recently been improved against HER2-positive advanced stomach cancer. Here, we examined whether Y-box-binding protein-1 (YB-1) could selectively control HER2 gene expression and cellular sensitivity to EGF receptor (EGFR) family protein-targeted drugs in human gastric cancer cells. HER2 expression was specifically downregulated by YB-1 silencing using its cognate siRNA, whereas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Tomohiro Shibata et al reported that silencing of YB-1 specifically down-regulates HER2 expression and induces lapatinib resistance in GC cells [26]. The data presented here indicated that sensitivity of lapatinib altered by JWA was dependent on HER2 expression.…”
Section: Discussionsupporting
confidence: 52%
“…Tomohiro Shibata et al reported that silencing of YB-1 specifically down-regulates HER2 expression and induces lapatinib resistance in GC cells [26]. The data presented here indicated that sensitivity of lapatinib altered by JWA was dependent on HER2 expression.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, afatinib-resistant sublclones are also cross-resistant to gefitinib and also lapatinib (Table 1). EGFR forms a duplex with HER2 or HER3 (31), and sensitivity to lapatinib is controlled through HER2 and/or EGFR (32, 33). The cross-resistance to lapatinib in afatinib-resistant sublclones might be due to marked downregulation of HER2/pHER2 and pEGFR/activated mutant EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of p-EGFR staining was evaluated according to the percentage of cells with strongly stained nuclei in 3 visual fields under a light microscope (x200). All immunohistochemistry studies were evaluated by 2 experienced observers who were blind to the conditions of the experiments as reported previously (35).…”
Section: Immunohistochemistry For Xenograft Tumor Specimensmentioning
confidence: 99%